The First Five Toilets Of Many: Piloting SANILAB in Quebrada Verde, Perú - Mytty, Kate (2016)
The project evolved from a collaboration between the Quebrada Verde community, located an hour outside of Lima, and D-Lab Perú, an organization inspired by MIT D-Lab (see blog, IDIN network member designs and launches new course in Peru based on IDDS experience) and initiated in a class at the Pontificia Universidad Católica del Perú (PUCP).